Treatment of Atypical Evolutions of Idiopathic Focal Epilepsies in Childhood - Fejerman, Natalio; Caraballo, Roberto H.; Flesler, Santiago (Journal of Pediatric Epilepsy, 2016)
The relationship between continuous spike-and-wave discharges during slow sleep (CSWSS) and neuropsychological impairment (cognitive functions, memory consolidation, and language and behavior disturbances) has been clearly demonstrated. These phenomena occur not only in symptomatic cases of CSWSS or electrical status epilepticus in sleep (ESES) syndrome, but also in the different conditions that constitute the spectrum of atypical evolutions of idiopathic focal epilepsies of childhood (IFEC). In spite of continuous advances in treatment, management is still difficult and challenging. Treatment options of atypical evolutions of IFEC include benzodiazepines, sulthiame, levetiracetam, valproic acid, and ethosuximide. Other drugs such as lacosamide and acetazolamide have been proposed. Usual antiepileptic drugs such as carbamazepine, phenobarbital, phenytoin, oxcarbazepine, lamotrigine, and topiramate were proven to be capable of inducing ESES. Steroids and intravenous immunoglobulins were recommended in refractory cases. Surgery, ketogenic diet, and vagal nerve stimulation were also used in some cases. Our interest regarding a scheme of treatment in atypical evolutions of IFEC is centered on two questions: (1) Is it possible to prevent the evolution of IFEC into atypical focal epilepsies of childhood, status epilepticus of IFEC, Landau–Kleffner's syndrome, or ESES syndrome? (2) Which is the treatment of choice once one of these conditions is installed?
Keywords: spike-and-wave; CSWSS; ESES; epileptic encephalopathies; BCECTS; LKS; Panayiotopoulos syndrome; treatment; sulthiame; levetiracetam